Codon decoding by orthogonal tRNAs interrogates the in vivo preferences of unmodified adenosine in the wobble position - Schmitt, Margaret A.; Tittle, Jillyn M.; Fisk, John D. (Frontiers in Genetics, 2024)
The in vivo codon decoding preferences of tRNAs with an authentic adenosine residue at position 34 of the anticodon, the wobble position, are largely unexplored because very few unmodified A34 tRNA genes exist across the three domains of life. The expanded wobble rules suggest that unmodified adenosine pairs most strongly with uracil, modestly with cytosine, and weakly with guanosine and adenosine. Inosine, a modified adenosine, on the other hand, pairs strongly with both uracil and cytosine and to a lesser extent adenosine. Orthogonal pair directed sense codon reassignment experiments offer a tool with which to interrogate the translational activity of A34 tRNAs because the introduced tRNA can be engineered with any anticodon. Our fluorescence-based screen utilizes the absolute requirement of tyrosine at position 66 of superfolder GFP for autocatalytic fluorophore formation. The introduced orthogonal tRNA competes with the endogenous translation machinery to incorporate tyrosine in response to a codon typically assigned another meaning in the genetic code. We evaluated the codon reassignment efficiencies of 15 of the 16 possible orthogonal tRNAs with A34 anticodons. We examined the Sanger sequencing chromatograms for cDNAs from each of the reverse transcribed tRNAs for evidence of inosine modification. Despite several A34 tRNAs decoding closely-related C-ending codons, partial inosine modification was detected for only three species. These experiments employ a single tRNA body with a single attached amino acid to interrogate the behavior of different anticodons in the background of in vivo E. coli translation and greatly expand the set of experimental measurements of the in vivo function of A34 tRNAs in translation. For the most part, unmodified A34 tRNAs largely pair with only U3 codons as the original wobble rules suggest. In instances with GC pairs in the first two codon positions, unmodified A34 tRNAs decode the C- and G-ending codons as well as the expected U-ending codon. These observations support the “two-out-of-three” and “strong and weak” codon hypotheses.